Education reform imaginaries: mapping -scapes of philanthropic influence. Issue 5 (3rd September 2021) - Miglani, Neha; Burch, Patricia
ABSTRACT: This paper unpacks the discursive work of global education philanthropies to shed light on how the work of educational actors inscribes and directs global forces, connections and imaginaries to specific local ends. We do so by analyzing the discursive work of two educational philanthropies – in the US and India – that are similar but also vary in ways related to their global reach and networks. Building on Appadurai's notions of -scapes we show the use of technocratic discourses in the construction and enablement of imagined educational futures of the socially disadvantaged. This paper speaks to theoretical concerns that often club broad concerns of globalization and neoliberalism in education and shows specific empirical openings that manifest as local choices and adaptations.